Clinical EFT as an evidence-based practice for the treatment of psychological and physiological conditions: A systematic review - Church, Dawson; Stapleton, Peta; Vasudevan, Anitha; O'Keefe, Tom (Frontiers in Psychology, 2022)
Background: Since the turn of the century, Emotional Freedom Techniques (EFT) has come into widespread use in medical and psychological treatment settings. It is also used as self-help by tens of millions of people each year. Clinical EFT, the manualized form of the method, has been validated as an “evidence-based” practice using criteria published by the American Psychological Association (APA) Division 12 Task Force on Empirically Validated Therapies. Its three essential ingredients are exposure, cognitive framing, and acupressure. Objectives: In 2013 we published a paper defining Clinical EFT and reviewing published research. It has been viewed or downloaded over 36,000 times, indicating widespread interest in this treatment modality. Here we update our findings based on subsequently published literature, and propose directions for future research. Method: We performed a systematic review of the literature to identify randomized controlled trials (RCTs) and meta-analyses. Retrieval of 4,167 results resulted in the identification of 56 RCTs (N=2,013), 41 of which were published subsequent to our earlier review, as well as eight meta-analyses. Results: RCTs have found EFT treatment to be effective for (a) psychological conditions such as anxiety, depression, phobias, and posttraumatic stress disorder (PTSD); (b) physiological issues such as pain, insomnia, and autoimmune conditions; (c) professional and sports performance; and (d) biological markers of stress. Meta-analyses evaluating the effect of EFT treatment have found it to be “moderate” to “large.” Next steps include determining its impact on cancer, heart disease, diabetes, and cognitive impairment; analysis of the large-scale datasets made possible by mobile apps; and delivery through channels such as virtual practitioner sessions, online courses, apps and standardized group therapy. Conclusions: Subsequent research has confirmed the conclusions of earlier studies. These find Clinical EFT to be efficacious for a range of psychological and physiological conditions. Treatment is associated with measurable biological effects in the dimensions of gene expression, brain synchrony, hormonal synthesis, and a wide range of biomarkers. Clinical EFT is an evidence-based stable and mature method and can be used in primary care settings as a safe, rapid, reliable, and effective treatment for both psychological and medical diagnoses continue to grow.